Pengaruh Model Active Debate dalam Pembelajaran Sejarah Terhadap Motivasi Belajar Mahasiswa - Nurjannah, Nurjannah; Khatimah, Husnul; Sumarni, Sumarni; Safran, Safran (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
So far, learning history has always been considered boring learning because it is synonymous with memorizing, even though according to some people learning history is very fun if accompanied by strategic accuracy and the use of learning models. According to Hariyano (1995: v-vi) that history in school institutions is not always interesting. Many students consider it to be chronic: One of the causes is the lack of mastery of historical material as well as the teaching methodology mastered by educators. Moreover, not all history subject holders have a historical educational background. In the process of developing learning motivation, students need to stimulate their ability to think logically and systematically. The active debate model can be used to eliminate boredom in students. Because the active debate model is a very important learning model for improving students' academic abilities. The aim of this research is to analyze the influence of learning motivation on history students at STKIP Yapis Dompu through the active debate learning model. The research results from the analysis results for hypothesis testing obtained using the SPSS 25 program are tcount -20.99 and ttable = -1.71 with df= 22, then based on the decision criteria if tcount > ttable or tcount < ttable so, -20.99 < -1.71 then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the active debate model on student learning motivation.